PENERAPAN PEMBELAJARAN MEDIA DIGITAL POWTOON UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS PADA SISWA KELAS IV DI UPT SDN 007 PULAU TINGGI - Kholidah Nasution, Henni; Mufarizuddin; Hana Pebriana, Putri; Marleni, Lusi; Yusnira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement of critical thinking skills through the application of digital media learning animated videos in Grade IV Students of UPT SDN 007 Pulau Tingg. This research is motivated by the low critical thinking skills of students in the learning process of Pancasila Education subjects in grade IV. This research is a Classroom Action Research (CAR), which is carried out in two cycles and each cycle consists of two meetings. The subjects in this study were 1 teacher and 20 grade IV students of SDN 007 Pulau Tinggi. While the object is the application of digital media learning animated videos and critical thinking skills in students. Data collection techniques using observation, testing, and documentation techniques. While the data analysis technique used is qualitative descriptive analysis with percentages. Based on the results of research and data analysis, it shows that learning digital media animated videos can improve students' critical thinking skills. This can be seen from before the action, the average critical thinking ability of students only reached 61.25 and was in the less critical category. Then after implementing digital media learning animated videos in cycle I, the average critical thinking ability of students increased to 71.75 and was in the fairly critical category. In cycle II, the average critical thinking ability of students increased further, reaching 85.0 or was in the critical category. Thus, it can be concluded that the talking stick learning model can improve students' critical thinking skills in the Pancasila Education subject of grade IV SDN 007 Pulau Tinggi.